2021
DOI: 10.2174/1570159x19666210203161559
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as a Promising Therapeutic Strategy for Peripheral Nerve Injury

Abstract: Peripheral nerve injury has a high incidence and often leads to severe losses of sensory and motor functions in the afflicted limb. Autologous nerve grafts are widely accepted as the gold standard for peripheral nerve repair, but the presence of inherent drawbacks dramatically reduces their usability. Numerous tissue engineering nerve grafts are developed as alternatives of autologous nerve grafts, and a variety of cells and neurotrophic factors were introduced into these grafts for improvement. However, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 125 publications
0
42
0
2
Order By: Relevance
“…The incidence of peripheral nerve injury (PNI) is very high, often leading to severe loss of sensory and motor function of the affected limb [ 127 ]. Autologous nerve transplantation is widely accepted as the gold standard for peripheral nerve repair, but its inherent defects greatly reduce their availability [ 128 ].…”
Section: Role and Application Of Exosomes In Specific Cns Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of peripheral nerve injury (PNI) is very high, often leading to severe loss of sensory and motor function of the affected limb [ 127 ]. Autologous nerve transplantation is widely accepted as the gold standard for peripheral nerve repair, but its inherent defects greatly reduce their availability [ 128 ].…”
Section: Role and Application Of Exosomes In Specific Cns Diseasesmentioning
confidence: 99%
“…Regeneration after peripheral nerve injury is still a major challenge for researchers and clinicians. Increasing evidence show that exosomes can play a neurotherapeutic effect by mediating axon regeneration, Schwann cell activation, angiogenesis and inflammation regulation [ 127 ]. Besides, peripheral nerve injury may cause neuropathic pain.…”
Section: Role and Application Of Exosomes In Specific Cns Diseasesmentioning
confidence: 99%
“…In the peripheral nervous system, Schwann cells secrete exosomes that are internalized by neighboring axons, providing local axonal support and enhancing axonal regeneration after nerve damage [91]. Gomez-Molina et al provide evidence of two-way communication through exosomes from the brain to the rest of the body [92].…”
Section: Exosomes In the Nervous Systemmentioning
confidence: 99%
“…It is thought that supplementing their natural function could enable targeted delivery of drug molecules (Mehryab et al, 2020). Multiple studies have confirmed that SC can secrete exosomes and that they have a powerful promotion effect on neuronal axon regeneration and improve neuronal viability (Hu et al, 2019;Yu et al, 2021). It was found that miRNA-21 expression was increased in secreted exosomes after SC upregulated the expression of c-jun and Sox2, which are key in promoting neurite growth by SC-derived exosomes (López-Leal et al, 2020).…”
Section: Sc Mechanisms For Neuronal Repair and Regenerationmentioning
confidence: 99%